The Implementation of Cooperative Integrated Reading and Composition (CIRC) in Teaching Reading Comprehension to the Ninth Grade Students (RETAIN, 2019)
Abstrak Penelitian ini dilakukan untuk mengetahui bagaimana penerapan teknik Cooperative Integrated Reading and Composition (CIRC), kemampuan siswa, dan respon siswa terhadap pengajaran membaca pemahaman dengan menggunakan CIRC. Penelitian ini menggunakan penelitian kualitatif untuk merancang penelitian ini. Dalam penelitian ini, peneliti mengamati aktivitas mata pelajaran. Peneliti hanya menggunakan catatan lapangan, kuesioner, dan tugas membaca siswa. Subjek penelitian ini adalah siswa kelas sembilan di SMPN 1 Jabon. Guru yang mengajar di kelas juga sebagai subjek penelitian. ini dipelajari karena dia juga bertanggung jawab untuk proses belajar mengajar menggambarkan bagaimana mengajar membaca teks menggunakan teknik Cooperative Integrated Reading and Composition (CIRC) di kelas sembilan di sekolah menengah pertama dilaksanakan. Hasil penelitian ini akan dipresentasikan melalui hasil observasi , tugas siswa, dan respons siswa melalui angket. Guru melakukan prosedur CIRC dengan sangat baik. Berdasarkan s tugas siswa, siswa dapat menjawab semua pertanyaan dengan benar. Berdasarkan tanggapan siswa terhadap teknik CIRC, mereka merasa percaya diri dan termotivasi ketika diajarkan menggunakan CIRC. Saran bagi guru adalah guru harus menerapkan CIRC dalam mengajar pemahaman membaca sebagai teknik alternatif. Tidak hanya dalam pengajaran label teks tetapi juga dalam teks lainnya. Kata kunci : Membaca pemahaman, Cooperative integrated reading and composition (CIRC). Abstract This study was conducted to know how the implementation of Cooperative Integrated Reading and Composition (CIRC) technique, students ability, and students responses toward teaching reading comprehension by using CIRC. This study use qualitative research to design this study. In this research, the researcher observes subjects activity. The researcher only used a field note, questionnaire, and students reading task. The subject of this study was the ninth grade students in SMPN 1 Jabon. The teacher who taught in the class was also as the subject of this studied because he was also responsible for the teaching-learning process of describing how is teaching reading text using Cooperative Integrated Reading and Composition (CIRC) technique in the ninth grade of junior high school implemented. The result of this study will be presented through observation result, students task, and students’ responses through a questionnaire. The teacher does the procedure of CIRC very well. Based on students tasks, the students are able to answer all questions correctly. Based on the students responses toward CIRC technique, they feel confident and motivated when taught using CIRC. The suggestion for the teacher is the teacher has to implement CIRC in teaching reading comprehension as an alternative technique. Not only in teaching label text but also in other text. Keyword: reading comprehension, Cooperative integrated reading and composition (CIRC).